THE RELATIONSHIP OF NURSES' KNOWLEDGE REGARDING EWS (EARLY WARNING SCORE) TOOLS AND THEIR APPLICATION TO PATIENTS AT SILOAM HOSPITAL MANADO - Hesky Frengky Ngongoloy; Siolan Puspitasari Tangkilisan; Engelin Megawati Maatuil (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2023)
Background: Early Warning Score (EWS) is a system for requesting help to overcome patient health problems early which is based on an assessment of changes in the patient's condition through systematic observation of all changes in the patient's physiology. Inconsistent implementation of EWS can be caused by decreased awareness of the importance of monitoring vital signs and the level of knowledge of nurses. Objective: To determine the relationship between nurses' knowledge regarding EWS tools and their application to patients at Siloam Manado Hospital. Method: This research is a correlational descriptive quantitative research with a cross sectional approach with a sample of 50 people. The sampling technique used purposive sampling, namely 50 people. Results: Based on the results of the chi square test, 40 respondents (95.2%) had high knowledge of the correct application of EWS, 6 respondents (75.0%) had low knowledge. The results of the bivariate test using the chi square test showed that the level of nurses' knowledge did not have a significant relationship with the implementation of EWS with a value of (p=0.000) supported by a contingency coefficient of 0.000. Future research should examine performance behavior by observing the population to see a more complete implementation of EWS. Keywords: Early warning score; Level of knowledge; implementation of EWS.